1998
DOI: 10.1182/blood.v92.11.4023.423k54_4023_4030
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Production Is Inhibited by a Translational Mechanism

Abstract: Thrombopoietin (TPO) is a lineage-dominant hematopoietic cytokine that regulates megakaryopoiesis and platelet production. The major site of TPO biosynthesis is the liver. Despite easily detectable levels of liver TPO mRNA, the circulating TPO serum levels are very low. We have observed that translation of TPO mRNA is inhibited by the presence of inhibitory elements in the 5′-untranslated region (5′-UTR). Alternative promoter usage and differential splicing generate at least three TPO mRNA isoforms that differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 46 publications
1
45
0
1
Order By: Relevance
“…4). Targeted mutagenesis (Ghilardi et al, 1998) confirmed that upstream AUG#7 is primarily responsible for blocking translation of TPO. This is because its near-optimal context (GCCGCCUCCaugG) prevents leaky scanning and the overlapping arrangement precludes reinitiation.…”
Section: Human Thrombopoietin -An Example Of Severely Restricted Tranmentioning
confidence: 90%
See 4 more Smart Citations
“…4). Targeted mutagenesis (Ghilardi et al, 1998) confirmed that upstream AUG#7 is primarily responsible for blocking translation of TPO. This is because its near-optimal context (GCCGCCUCCaugG) prevents leaky scanning and the overlapping arrangement precludes reinitiation.…”
Section: Human Thrombopoietin -An Example Of Severely Restricted Tranmentioning
confidence: 90%
“…that view (Kozak, 2001b). Indeed many studies have shown that the strongest inhibition is caused by an upORF that overlaps the start of the downstream cistron (Babik et al, 1999;Bates et al, 1991;Byrne et al, 1995;Cao and Geballe, 1995;Ghilardi et al, 1998;Hansen et al, 2002;Kos et al, 2002;Lee et al, 1999;Liu et al, 1999), which would not be the case if ribosomes could move backwards to reinitiate.…”
Section: Definition and General Rulesmentioning
confidence: 99%
See 3 more Smart Citations